Limited Physiological Compensation in Response to an Acute Microclimate Change in a Malagasy Bat - Reher, Stephanie; Rabarison, Hajatiana; Nowack, Julia; Dausmann, Kathrin H. (Frontiers in Ecology and Evolution, 2022)
Rapid environmental changes are challenging for endothermic species because they have direct and immediate impacts on their physiology by affecting microclimate and fundamental resource availability. Physiological flexibility can compensate for certain ecological perturbations, but our basic understanding of how species function in a given habitat and the extent of their adaptive scope is limited. Here we studied the effect of acute and experimental microclimate change on the thermal physiology of two populations of the widespread Malagasy bat, Macronycteris commersoni. Populations of this species are found roosting under contrasting conditions, i.e. in a constant hot and humid cave or below foliage unprotected from fluctuations in ambient conditions. We exposed free-ranging individuals of each population to the respective opposite condition and thus to novel microclimate within an ecologically realistic scope while measuring metabolic rate and skin temperature. Cave bats in forest setting had a limited capacity to maintain euthermia to the point that two individuals became hypothermic when ambient temperature dropped below their commonly experienced cave temperature. Forest bats on the other hand, had difficulties to dissipate heat in the humid cave set-up. The response to heat, however, was surprisingly uniform and all bats entered torpor combined with hyperthermia at temperatures exceeding their thermoneutral zone. Thus, while we observed potential for flexible compensation of heat through “hot” torpor, both populations showed patterns suggestive of limited potential to cope with conditions deviating from their typically occupied microclimates. Our study emphasizes that intraspecific variation among populations could be misleading when assessing species’ adaptive scopes, as variation may arise from genetic adaptation, developmental plasticity or phenotypic flexibility, all of which allow for compensatory responses at differing time scales. Disentangling these mechanisms and identifying the basis of variation is vital to make accurate predictions of species’ chances for persisting in ever rapidly changing habitats and climates.